Superhero kindergarten. How the Super K's save Christmas [videorecording (DVD)] (NCircle Entertainment, 2022)
Super K to the Rescue! Greenville Elementary and the Academy for Superior Children battle it out for the annual prize of Best Kindergarten Holiday Show. After Nigel Danforth and the Fearsome Foursome do everything they can to wreck the Super K's show, Mr. Arnold Armstrong and the kids are sure they'll lose. When things don't turn out quite as Danforth had hoped, he hatches a plan to get rid of Christmas once and or all. It's up to the Super K's to stop them!